2018
DOI: 10.1002/cmdc.201800428
|View full text |Cite
|
Sign up to set email alerts
|

d‐Polyarginine Lipopeptides as Intestinal Permeation Enhancers

Abstract: An estimated 285 million people were living with diabetes in 2010, and this number is expected to reach 440 million by 2030. Current treatment of this disease involves the intradermal injection of insulin analogues. Many alternative administration routes have been proposed, the oral route being the most widely studied. One of the most interesting approaches for insulin delivery is the use of permeation enhancers to increase its transport across the gastrointestinal tract (GIT). Cell-penetrating peptides (CPPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Conjugation of CPPs with clinically relevant molecules was reported. Examples include the combination of lipo-polyarginine with insulin that was shown to enhance the transport through Caco-2/HT-29 cells almost two-fold (Garcia et al, 2018). Moreover, the conjugation or co-administration of TAT and polynonaarginin with the parathyroid hormone has sharply increased the transport through Caco-2 cells (Kristensen et al, 2015).…”
Section: Barriers For the Therapeutic Use Of Ampsmentioning
confidence: 99%
“…Conjugation of CPPs with clinically relevant molecules was reported. Examples include the combination of lipo-polyarginine with insulin that was shown to enhance the transport through Caco-2/HT-29 cells almost two-fold (Garcia et al, 2018). Moreover, the conjugation or co-administration of TAT and polynonaarginin with the parathyroid hormone has sharply increased the transport through Caco-2 cells (Kristensen et al, 2015).…”
Section: Barriers For the Therapeutic Use Of Ampsmentioning
confidence: 99%
“…However, some studies indicate that poly- l -arginine can act as a permeation enhancer and transiently increase epithelial permeability by opening paracellular tight junctions. 15 Salmon protamine ( M w 372 Da) included in PrNC and PSA-PrNC as well as in approved insulin formulations has been reported to act as a cell-penetrating peptide (CPP), 27 and as a permeation enhancer. 28 This can be explained by arginine-rich sequences in the protamine peptide sharing homology to the canonical cell-penetrating peptide, Trans-Activator of Transcription (TAT).…”
Section: Resultsmentioning
confidence: 99%
“… 17 ENCP ( Figure 2 ) included C12-R8, octarginine (R8) linked to lauric acid (C12), a medium chain fatty acid. 15 R8 is a cell-penetrating peptide derived from the TAT sequence that has been reported to aid insulin intestinal permeability when complexed with it. 29 C12 is also an intestinal epithelial permeation enhancer, and it was included to aid R8-mediated epithelial permeation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, arginine-rich CPPs, (minimum amount of six Arg) are well known for their ability to cross biological barriers [ 49 , 50 ]. Although other studies have reported the conjugation of nanoparticles with internalization peptides in a direct way [ 51 , 52 , 53 , 54 ], it is also well known that the presence of BSA improves the circulation time of nanoparticles and controls the composition of the protein corona in physiological media, hence the importance of the inclusion of albumin in nanoparticles [ 37 , 55 , 56 ]. Therefore, we functionalized the BSA protein with r 8 to facilitate cell penetration of the AuNPs.…”
Section: Introductionmentioning
confidence: 99%